Aptamer-Conjugated Nanoparticles for Cancer Cell Detection - Medley, Colin D. (2011)
Aptamer-conjugated nanoparticles (ACNPs) have been used for a variety of applications, particularly dual nanoparticles for magnetic extraction and fluorescent labeling. In this type of assay, silica-coated magnetic and fluorophore-doped silica nanoparticles are conjugated to highly selective aptamers to detect and extract targeted cells in a variety of matrices. However, considerable improvements are required in order to increase the selectivity and sensitivity of this two-particle assay to be useful in a clinical setting. To accomplish this, several parameters were investigated, including nanoparticle size, conjugation chemistry, use of multiple aptamer sequences on the nanoparticles, and use of multiple nanoparticles with different aptamer sequences. After identifying the best-performing elements, the improvements made to this assay’s conditional parameters were combined to illustrate the overall enhanced sensitivity and selectivity of the two particle assay using an innovative multiple aptamer approach, signifying a critical feature in the advancement of this technique.